2015
DOI: 10.4141/cjas-2014-154
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fenugreek seed extract improves performance and reduces fecal E. coli counts and fecal gas emission in lactating sows and suckling piglets

Abstract: I. H. 2015. Dietary fenugreek seed extract improves performance and reduces fecal E. coli counts and fecal gas emission in lactating sows and suckling piglets. Can. J. Anim. Sci. 95: 561Á568. This study evaluated the efficacy of fenugreek seed extract (FSE) in sows and suckling piglets. The trial was conducted with 78 multiparous sows and their litters in a 28-d feeding trial, and one of three diets: CON (control, basal diet); FSE1 (basal diet'0.1% FSE), and FSE2 (basal diet'0.2% FSE). Piglets suckling sows fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(46 citation statements)
references
References 43 publications
4
41
1
Order By: Relevance
“…Dietary MOE supplemented sows were significantly effective on BW change and the relevant result of effect was tendency to reduction of body weight loss in lactation period, which result consistent with Mohana Devi et al (2016) reported that the effect of dietary supplement with protected organic acids on reproductive performance in sows. This perhaps is a consequence of improved intake and utilisation of food supplements with no relationship with sow back fat loss during lactation as suggested with previous reports (Ilsley et al 2003;Matysiak et al 2012;Kingori 2012;Chengquan et al 2015;Hossain et al 2015).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Dietary MOE supplemented sows were significantly effective on BW change and the relevant result of effect was tendency to reduction of body weight loss in lactation period, which result consistent with Mohana Devi et al (2016) reported that the effect of dietary supplement with protected organic acids on reproductive performance in sows. This perhaps is a consequence of improved intake and utilisation of food supplements with no relationship with sow back fat loss during lactation as suggested with previous reports (Ilsley et al 2003;Matysiak et al 2012;Kingori 2012;Chengquan et al 2015;Hossain et al 2015).…”
Section: Discussionmentioning
confidence: 51%
“…Proper nutritional administration of sows during gestation and lactation is significant for achieving and maintaining adequate sow productivity, longevity and litter performance (Kuller et al 2004;Oliviero et al 2009Hossain et al 2015). In the present study, it was hypothesised that feeding gestating and lactating sows a diet supplemented with MOE would confer beneficial effects to the sow by enhancing BWG, nutrient digestibility, manipulation of intestinal microbiota, and that such benefits would be passed on to the suckling piglets, as previously reported (Ilsley et al 2003;Matysiak et al 2012;Rossi and Soares 2013;Chengquan et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Faecal samples were collected directly via massaging the rectum of two pigs (one gilt and one barrow) from each pen on days 0 and d 42 and then pooled and transported to the laboratory, where microbial analysis was immediately carried out according to the method described by Li and Kim () and Hossain et al. (). One gram of the composite faecal sample from each pen was diluted with 9 ml of 1% peptone broth (Becton, Dickinson, Franklin Lakes, NJ) and then homogenized.…”
Section: Methodsmentioning
confidence: 99%
“…It has several beneficial properties, including reducing blood sugar level (Raghuram et al., ), and anti‐inflammatory, antipyretic (Ahmadiani et al., ) and antimicrobial (Windisch et al., ) activities. Fenugreek is also reported to have antidiabetic and hypocholesterolemic effects (Al‐Habori and Roman, ; Windisch et al., ; Hossain et al., ). These effects might be attributed to saponins that have been shown to be able to improve the growth performance of broilers, chickens and fish (Johnston et al., ; Francis et al., , ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that dietary supplementation with extracts of some plants increased egg production, feed conversion ratio, and egg weight in laying hens (Uuganbayar et al, 2005;Nadia et al, 2008;Radwan et al, 2008). Recent reports have also suggested an improvement in the early growth performance of broilers and pigs, when supplemented with FSE (Hossain et al, 2015;Park and Kim, 2016). In contrast, previous studies have shown that neither PFA nor FSE exhibited significant effects on feed intake, feed efficiency, and/or egg production of laying hens (Botsoglou et al, 2005;Deng et al, 2012;Al-Aqil, 2016).…”
Section: Discussionmentioning
confidence: 73%